Kualitas Rasa Solidaritas dalam Perspektif Emile Durkheim: Studi Kasus Aktivitas Dakwah Pemuda Persis Ciganitri - Rizqi Faisal Muzaqi (Gunung Djati Conference Series, 2023)
This study aims to discuss the quality of the sense of solidarity found in Persis Youth in Ciganitri with the theory of solidarity expressed by Emile Durkheim. This research uses a qualitative approach through literature and field studies. The formal object of this research is Emile Durkheim's theory of solidarity. While the material object is the youth missionary activity of Persis. The context of this research is the social organization Persis in Ciganitri. Starting with describing the da'wah activities of Persis Youth in Ciganitri, Durkheim's idea of solidarity and also analyzing the sense of solidarity using Durkheim's perspective. The results of the discussion show that solidarity in society in Durkheim's view is divided into two types, namely mechanical and organic solidarity. This study concludes that the sense of solidarity possessed by Persis Youth in Ciganitri is still in a position of mechanical solidarity, even though Persis Youth in Ciganitri has become a modern society.